Evaluation of Urinary Purine Derivatives Creatinine Index as a Predictor of the Nutritional Status in Dairy Animals at Farm Level - Singh, V. K.; Singh, P.; Verma, A. K.; Mehra, U. R. (Indian Journal of Animal Nutrition, 2017)
A total of 120 farmers were selected as per stratified random design from eastern plain zone (UP-9) of Middle Gangetic Plains region to investigate the effectiveness of spot urine purine derivatives creatinine (PDC) index as a predictor of nutritional status of dairy animals at farm level. A bench mark survey was conducted to gather first hand information regarding the nutritional status of dairy animals (60 cattle and buffaloes each). Itcomprised data collection through questionnaire as well as collection of feed samples and spot urine samples. The data were again categorized into landless (n=24), marginal (n=24), small (n=24), medium (n=24) and large (n=24) farmer categories. The mean concentration of total purine derivatives (PD) in spot urine was higher in cattle than buffaloes ((14.08 vs. 3.20 mmol/L). The total PD level showed significant (P